Exploring flow rate selection in HIPEC procedures - BATISTA,THALES PAULO (2016)
ABSTRACT Cytoreductive surgery (CRS) plus hyperthermic intraperitoneal chemotherapy (HIPEC) has emerged as a main comprehensive treatment of peritoneal malignancies. However, current data on the literature are very heterogeneous in terms of its technical particularities, which require some efforts to standardization of practices. In these setting, we present some early data from a pioneering clinical trial in Brazil (ClinicalTrials.gov Identifier: NCT02249013) to explore the dynamic relationships between flow rates and temperature parameters in the first cases of our study, which may help in selecting better technical parameters during HIPEC procedures.